2015
DOI: 10.1136/thoraxjnl-2015-207770.207
|View full text |Cite
|
Sign up to set email alerts
|

P70 Blood eosinophil counts in normal controls with no history of allergic disease

Abstract: BackgroundThe beneficial effect of corticosteroids and anti-interleukin (IL)-5 on exacerbations of airway disease becomes apparent at blood eosinophil counts above 0.15 × 109/L, well within the normal range. One potential explanation is that the upper limit of the normal range is artificially high because studies have included patients with allergic disease and eosinophilic inflammation. We have assessed the normal range for blood eosinophil counts in volunteers with no self-reported history of allergic diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Up to 40% of the general population have been found to have atopy 52 . In a small calibration study 47 , the circulating eosinophil count mean and upper limit of normal (95% upper limit) reference range for all healthy controls was found to be 190 (420) cells/μL. Repeated reference laboratory calibration, in a separate healthy control population, where atopic (self-reported or elevated IgE) controls were excluded, demonstrated that the mean (95% upper limit) circulating eosinophil count was 150 (270) cells/μL.…”
Section: The Eosinophil As a Relevant And Valid Biomarker In Copdmentioning
confidence: 95%
See 1 more Smart Citation
“…Up to 40% of the general population have been found to have atopy 52 . In a small calibration study 47 , the circulating eosinophil count mean and upper limit of normal (95% upper limit) reference range for all healthy controls was found to be 190 (420) cells/μL. Repeated reference laboratory calibration, in a separate healthy control population, where atopic (self-reported or elevated IgE) controls were excluded, demonstrated that the mean (95% upper limit) circulating eosinophil count was 150 (270) cells/μL.…”
Section: The Eosinophil As a Relevant And Valid Biomarker In Copdmentioning
confidence: 95%
“…Peripheral blood eosinophil counts in asthma, chronic obstructive pulmonary disease and healthy controls. Data derived from Bafadhel et al 42 and Anand et al 47 For a biomarker to be relevant and valid, although not in the original biomarker definitions described above by the WHO 34 , its presence needs to be stable or repeatable over time. This is essential when considering life-long or expensive treatment options based upon the presence or level of the relevant biomarker i.e.…”
Section: The Eosinophil As a Relevant And Valid Biomarker In Copdmentioning
confidence: 99%
“…In retrospect, it makes sense that peripheral eosinophilia might reflect sputum eosinophilia, but this straightforward measure may have obscured by potentially clinically useful measurements being in the ‘normal’ range. It is worth noting that ‘normal’ ranges were calculated using both atopic and non‐atopic individuals; recalculating without atopic patients reduces the normal range to around the level reflective of sputum eosinophilia . The important clinical question is of course ‘is it useful’, rather than ‘is it normal?’ Can blood eosinophils help titrate therapy like sputum eosinophils?…”
Section: Asthmamentioning
confidence: 99%
“…It is worth noting that 'normal' ranges were calculated using both atopic and non-atopic individuals; recalculating without atopic patients reduces the normal range to around the level reflective of sputum eosinophilia. 31,32 The important clinical question is of course 'is it useful', rather than 'is it normal?' Can blood eosinophils help titrate therapy like sputum eosinophils?…”
Section: Environment As a Trigger Of Lung Diseasementioning
confidence: 99%
“… 2 Recently, the median eosinophil count in health was shown as 0.11 × 10 9 /l and 0.15 × 10 9 /l (with an upper limit of normal range at 0.27 × 10 9 /l). 34 In asthma, corticosteroid and anti‐IL‐5 anti‐eosinophil treatment response is seen in patients with eosinophils at 0.15 × 10 9 /l. 5 Blood levels of ≥250 cells/l (ie 0.25 × 10 9 /l) are the current set criteria for selection of CRS patients for biologics that target key T2 inflammatory signalling points.…”
Section: Introductionmentioning
confidence: 99%